Oral celecoxib and tramadol after 24 hours in patients undergoing major operation in kuantan: a randomized comparattve study - Mohamed, Rozilah @ Abdul Hadi; Abdullah, Nor Zamzila; Mokhtar, Md Lukman; Osman, Ariff; Mat Nor, Mohd Basri (2007)
Introduction: Tramadol is a weak opioid analgesic, acting mainly on μ-opioid receptor and has been proven to be effective and safe analgesic used for use in post-operative patients. Whereas celecoxib is a highly selective COX-2 inhibitor belonging to the non-steroidal anti-inflammatory drugs (NSAIDs) group which reduces inflammation and pain while minimizing gastrointestinal adverse reactions. This selectivity feature makes celecoxib an attractive alternative to opioids for the control of postoperative pain.